2017
DOI: 10.4103/ojo.ojo_234_2014
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of prematurity: Revisiting incidence and risk factors from Oman compared to other countries

Abstract: Purpose:The purpose of this study is to determine the incidence of retinopathy of prematurity (ROP) and the maternal/neonatal risk factors at a tertiary care hospital in Oman, compared to other countries.Patients and Methods:A retrospective analysis of premature neonates born with gestational age (GA) 24–32 weeks at Sultan Qaboos University Hospital, Oman, from January 2007 to December 2010. Maternal and neonatal in-hospital course was retrieved. The incidence of ROP was reported. Risk factors analyses were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…As mentioned above, sepsis can be classified as early or late and as bacterial or fungal. Since most of the original studies performed fundus examinations for ROP screening 4~6 weeks after birth, only two studies27 28 provided findings that might include late-onset sepsis. It is difficult for us to distinguish whether these patients had early-onset or late-onset sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, sepsis can be classified as early or late and as bacterial or fungal. Since most of the original studies performed fundus examinations for ROP screening 4~6 weeks after birth, only two studies27 28 provided findings that might include late-onset sepsis. It is difficult for us to distinguish whether these patients had early-onset or late-onset sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…[58,60] Thus, it is important to adjust for the influence of oxygen and mechanical ventilation on the relationship of sepsis and ROP. However, of the 34 studies included, only 7 studies [22,26,33,35,36,40,44] had concurrently adjusted for this 2 factors. In addition, although there are 14 studies which adjusted the confounder of oxygen use, the bias may still exist because it is difficult to adjust appropriately for oxygenation to normalizing the oxygenation among studies.…”
Section: Discussionmentioning
confidence: 99%
“…328 These results have been replicated in multiple subsequent studies, both for the risk of incident ROP and of treatment-requiring ROP. 6,10,11,13,14,17,18,21,47,57,65,75,77,94,102,109,114,122,125,135,138,143,147,152,157,174,202,204,216,228,231,233,236,240,246,255,263,266,271,276,282,283,285,308,311,312,315,335,337,348,362,367,371,373,378,391,398,405,406,410,412,418…”
Section: Major Risk Factorsmentioning
confidence: 99%
“…88,419 A number of subsequent studies found the duration of oxygen therapy to be a significant risk factor for severe ROP. 10,13,39,57,71,74,109,114,131,149,152,167,231,236,257,264,276,283,312,313,315,364,401,412,428 Similarly, many studies identified prolonged mechanical ventilation as a risk factor for any or severe ROP. 11,12,36,39,53,57,106,120,157,167,187,211,232,263,266,274,275,286,335,337,345,348,368,370,405,406,412,417…”
Section: Major Risk Factorsmentioning
confidence: 99%